2008
DOI: 10.1093/nar/gkn884
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bacterial transformation efficiency using plasmid artificial modification

Abstract: We have developed a method to improve the transformation efficiency in genome-sequenced bacteria, using ‘Plasmid Artificial Modification’ (PAM), using the host's own restriction system. In this method, a shuttle vector was pre-methylated in Escherichia coli cells, which carry all the putative genes encoding the DNA modification enzymes of the target microorganism, before electroporation was performed. In the case of Bifidobacterium adolescentis ATCC15703 and pKKT427 (3.9 kb E. coli-Bifidobacterium shuttle vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 14 publications
2
93
0
Order By: Relevance
“…Given the low electroporation frequencies for plasmid transfer into bifidobacteria, a number of studies on optimization of electroporation were undertaken, with limited success (9,253). Recently, methylating plasmids to overcome restriction systems in bifidobacteria were found to greatly improve transformation efficiencies (195,348).…”
Section: Development Of Cloning and Expression Vector Systems For Bifmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the low electroporation frequencies for plasmid transfer into bifidobacteria, a number of studies on optimization of electroporation were undertaken, with limited success (9,253). Recently, methylating plasmids to overcome restriction systems in bifidobacteria were found to greatly improve transformation efficiencies (195,348).…”
Section: Development Of Cloning and Expression Vector Systems For Bifmentioning
confidence: 99%
“…The genes encoding the R-M systems described above are frequently found in bifidobacterial genomes, and they are among (195,348). This greatly improved transformation efficiencies, to a level that permitted targeted mutagenesis in bifidobacteria (195).…”
Section: R-m Systemsmentioning
confidence: 99%
“…The uptake of pGLO plasmid is enhanced in the presence of CaCl 2 aided by heat shock, which increases the competence of the bacterial cells to take up extraneous genetic material (Cohen et al 1972;Bergmans et al 1981). The competence of the bacteria is also reported to be increased by other methods such as electroporation, (Dower et al 1998) plasmid artificial modification (Yasui et al 2009) and micro-shock waves (Divya et al 2011). Transformation with pGLO plasmid expresses b-lactamase enzyme.…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 99%
“…22,25,26) Most bacteria have specific R-M systems that function as defense mechanisms against invasion by foreign DNA from infected phages or conjugative plasmids. 27,28) Specific potent R-M systems inhibit the transformation of cells when foreign plasmid DNA is introduced. Yasui et al have reported that the transformation efficiency of Bifidobacterium adolescentis ATCC15703 increased from 10 0 CFU/mg DNA to 10 5 CFU/mg DNA when shuttle vector pKKT427 modified with specific methylases was used.…”
Section: Complementation Of Pyrf and Transformation Efficiencymentioning
confidence: 99%
“…Yasui et al have reported that the transformation efficiency of Bifidobacterium adolescentis ATCC15703 increased from 10 0 CFU/mg DNA to 10 5 CFU/mg DNA when shuttle vector pKKT427 modified with specific methylases was used. 28) In our previous study, we used two specific putative methylase genes from M. thermoacetica ATCC39073 in order to reduce the restriction activity of the recipient cells. 17) These two putative methylases could not be amplified using PCR in strains Y72 and Y73 (data not shown).…”
Section: Complementation Of Pyrf and Transformation Efficiencymentioning
confidence: 99%